Effects of ozone on the pain and disability in patients with failed back surgery syndrome - Barbosa,Danilo Costa (2017)
Summary Introduction: Low back pain is one of the painful disorders of higher prevalence. It has several etiologies and surgery may be indicated in the presence of neurological deficits or compression syndromes. However, in up to 40% of cases, patients develop worsening of pain and failed back surgery syndrome (FBSS), which is an important cause of chronic pain with high morbidity and disability. In the last two decades, ozone has been shown to be a new therapeutic option for FBSS due to its analgesic and anti-inflammatory properties. Objective: To evaluate the effect of ozone therapy on pain and disability in patients with failed back surgery syndrome. Method: We selected 19 patients undergoing epiduroscopy and injection of ozone. Patients were evaluated preoperatively and 21 days after the procedure, using the following instruments: Visual Analogue Scale (VAS), Brief Pain Inventory, Roland-Morris Questionnaire Disability, Oswestry Disability Index (ODI), Neuropathic Pain Symptom Inventory and Douleur Neuropathique 4. Results: The patients showed significant pain relief, but no improvement was observed in the functional scales. Conclusion: Our results suggest that epidural ozone therapy can be a treatment option in FBSS to reduce the intensity of the pain.